The Effect of a Proposed Educational Program Using Kinesthetic Storytelling on the Basic Motor Skills Grade One Students in Sultanate of Oman - Al-Siyabi, Alya Masaud Hamdoon; Al-Hadabi, Badria Khalfan (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the effect of an educational program using the movement story on some basic motor skills for the first grade. The sample consisted of 56 students from Al-Fayhaa School in Al-Dakhiliyah Governorate, and the application took nine weeks during the academic year 2016/2017.To verify the hypotheses of the study, the experimental method was used, an educational program was built using the movement story, and pre and post tests were conducted for skills (running, jumping, throwing, catching, static balance, moving balance). The results indicated that there were statistically significant differences at the level of 0.05 between the experimental and control groups in the post-measurement in motor skills in favor of the experimental group, and there were statistically significant differences at the level of 0.05 between the pre- and post-measurement of the experimental and control groups in motor skills in favor of the post-measurement. Except for the skill of running, and this is because of the educational program using the dynamic story, and the researcher recommends directing the first cycle teachers to use the dynamic story in the teaching process.
Keywords: motor story; motor skills